2006
DOI: 10.1111/j.1445-2197.2006.03908.x
|View full text |Cite
|
Sign up to set email alerts
|

Perforated Diverticulitis Managed by Laparoscopic Lavage

Abstract: Laparoscopic lavage and drainage in the acute management of perforated acute diverticulitis may be a promising alternative to more radical procedures, including the Hartmann's procedure. Acute resection should still be carried out in patients found to have faecal peritonitis or who fail to improve following lavage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 10 publications
(36 reference statements)
4
63
0
4
Order By: Relevance
“…In addition, laparoscopic lavage was safely performed for fecal peritonitis (Hinchey grade IV) in some studies [19,20]. However, another study showed that laparoscopic lavage for patients with fecal peritonitis failed and required a subsequent Hartmann's procedure [21]. Intra-peritoneal massive irrigation played an important role in patients with fecal contamination associated with dilute bacterial mass [22].…”
Section: Discussionmentioning
confidence: 98%
“…In addition, laparoscopic lavage was safely performed for fecal peritonitis (Hinchey grade IV) in some studies [19,20]. However, another study showed that laparoscopic lavage for patients with fecal peritonitis failed and required a subsequent Hartmann's procedure [21]. Intra-peritoneal massive irrigation played an important role in patients with fecal contamination associated with dilute bacterial mass [22].…”
Section: Discussionmentioning
confidence: 98%
“…The first published study of patients undergoing laparoscopic lavage for generalized purulent peritonitis due to perforated diverticular disease reported that all eight patients made a complete recovery, with no patient requiring further surgical intervention in the 12-to 48-month follow-up period [47]. Subsequent small series also concluded that laparoscopic lavage is a safe and effective alternative to colectomy in patients with diffuse purulent peritonitis [48][49][50][51][52][53][54][55]. The largest published series to date included 100 patients with generalized peritonitis and radiological evidence of pneumoperitoneum [56]; 92 of these were managed by laparoscopic lavage, and all eight patients with faecal peritonitis were converted to an open Hartmann's procedure.…”
Section: The Role Of Laparoscopic Peritoneal Lavagementioning
confidence: 99%
“…La experiencia inicial ha sido prometedora con respecto a la mortalidad perioperatoria y las complicaciones 30 . Es más, si bien la mayoría de los que proponen el LPL inicial, proponen una sigmoidectomía electiva diferida 33,[37][38][39][40] , un estudio multicéntrico irlandés reportó alentadores resultados luego del lavado seguido de una observación continua. De hecho, Myers 41 , encontró recurrencia de diverticulitis de sigmoides en 4 de 92 pacientes tratados, ninguno de los cuales requirieron cirugía en el seguimiento de hasta 36 meses.…”
Section: Alternativas De Manejo Quirúrgico Para La Diverticulitis Aguunclassified